Sustainable Harvest of Large Pelagic Fish in the Western Sumatra Sea - Hutagaol, Desta; Firmansyah, Firmansyah (Aquatic Life Sciences, 2025)
Large pelagic fish such as tuna, skipjack, and mackerel are key export commodities for fishers at Bungus Oceanic Fishing Port due to high demand and their importance in processed fish products. This study analyzed trends, sustainable potential, and utilization levels of these resources in the western Sumatra Sea. Research conducted from March 17 to April 1, 2023, used a descriptive quantitative survey and literature review, with catch and effort data from 2015 to 2022 processed using Microsoft Excel. Results showed increasing catch trends, with tuna, skipjack, and mackerel projected to reach 723,417 kg, 462,205 kg, and 706,592 kg by 2025, respectively. The Maximum Sustainable Yield (MSY) estimates were 532,728 kg/year for tuna, 1,047,319 kg/year for skipjack, and 10,445,616 kg/year for mackerel. On average, the utilization rate was 37%, with a fishing effort rate of 24%, both categorized as moderate. Although tuna catches exceeded the MSY in 2021 (109.55% utilization), average exploitation across species remained sustainable. These findings suggest current fishing practices have not yet surpassed ecological limits, providing room for controlled increases in fishing efforts to maximize yields while maintaining ecological balance.